2022
DOI: 10.1364/prj.445855
|View full text |Cite
|
Sign up to set email alerts
|

Exceptional points and enhanced nanoscale sensing with a plasmon-exciton hybrid system

Abstract: Singularities in the spectra of open systems, known as exceptional points (EPs), have been shown to exhibit nontrivial topological properties and enhanced sensitivities. Here, we propose a novel approach to realize the EPs in a plasmon-exciton hybrid system and explore their applications in enhanced nanoscale sensing technology. We consider a plasmon-exciton system composed of a gold nanorod and a monolayer WSe 2 . By controlling the geometric parameters o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…The complex frequency information is extracted by fitting the transmission spectra using a doublet Lorentz model (see Section S6 in the Supporting Information). [ 39 ] The blue and red dots represent the real and imaginary parts of the complex frequencies when the angular position of the object is changed. It is found that the frequency splitting (real part) and the difference in linewidth (imaginary part) alternate periodically between maximum and minimum.…”
Section: Enhanced Sensingmentioning
confidence: 99%
“…The complex frequency information is extracted by fitting the transmission spectra using a doublet Lorentz model (see Section S6 in the Supporting Information). [ 39 ] The blue and red dots represent the real and imaginary parts of the complex frequencies when the angular position of the object is changed. It is found that the frequency splitting (real part) and the difference in linewidth (imaginary part) alternate periodically between maximum and minimum.…”
Section: Enhanced Sensingmentioning
confidence: 99%
“…While EPs have been extensively investigated in bulky photonic designs [12][13][14][15], their exotic functionalities in nanophotonic non-Hermitian plasmonic systems still remain relatively unexplored. Some recent notable efforts towards this goal are the investigation of active and passive metallic gratings [16,17], plasmonic nanostructures [18][19][20][21], graphene [22,23], and epsilon-near-zero materials [24][25][26][27][28]. An alternative promising class of nanophotonic non-Hermitian scatterers are core-shell plasmonic nanoparticles loaded with active (gain) materials.…”
Section: Introductionmentioning
confidence: 99%
“…A plethora of intriguing effects and exotic phenomena emerge around EPs due to their nontrivial topological properties and the dimensionality reduction, including ultrasensitive sensing [6][7][8][9][10][11][12], laser mode selection [13,14], chiral mode conversion [15][16][17][18], and unidirectional invisibility [19,20]. Harnessing these peculiar features of non-Hermitian degeneracies for building novel devices with unprecedented performance has been experimentally demonstrated in various classical dissipative platforms, ranging from nanophotonics [2,[21][22][23][24][25], acoustics [26] to macroscopic facilities, such as fiber network [27], electric circuits [28] and heat diffusive system [29]. In recent years, great efforts have been dedicated to accessing the quantum EPs by implementing the non-Hermiticity in quantum systems [11,[30][31][32][33][34][35][36][37][38][39][40][41], and investigating the quantum states control through EPs [18, 33-35, 40, 42-44].…”
Section: Introductionmentioning
confidence: 99%